Nutrition quality and microbial content of buffalo, cow, and goat milk from West Sumatera - S. Melia; . Yuherman; . Ferawati; . Jaswandi; H. Purwanto; E. Purwati (Jurnal Ilmu Ternak dan Veteriner, 2018)
The aim of this research was to determine the quality of fresh milk physically, chemically and microbiologically obtained from cow, goats and buffalo in West Sumatra. The research method applied was laboratory experimental to analyze nutritional value, the number of aerobic bacteria and lactic acid bacteria, isolating and identifying lactic acid bacteria. Results showed that the nutritional value of milk had meet the requirements of Indonesian National Standardization, but the total colony of aerobic bacteria was above the allowed threshold of 1 x 106 CFU/ml. In addition, each sample had a total colony of varied lactic acid bacteria (LAB). The lowest total LAB value obtained in cow's milk was 0.84±0.18 x107 CFU/ml, in contrast to buffalo milk and goat milk which had a higher total LAB of 36.8±17.57 x107 CFU/ ml and 57.25±8.89 x107 CFU/ml. However, all the colonies showed almost identical morphology of LAB isolates. It is concluded that fresh milk from West Sumatra contains LAB therefore sanitation control is still needed during handling of milk.